Soil physical strength rather than excess ethylene reduces root elongation of Eucalyptus seedlings in mechanically impeded sandy soils - Benigno, S.; Cawthray, G.; Dixon, Kingsley; Stevens, J. (2012)
Seedling establishment in heavily compact soils is hampered by poor root growth caused by soil chemical or physical factors. This study aims to determine the role of ethylene in regulating root elongation through mechanically impeded sandy soils using Eucalyptus todtiana F. Muell seedlings. Concentrations of ethephon (1, 10, and 100 µM) were added to non-compact soils, and endogenous ethylene production from seedling roots was compared to ethylene production of roots grown in physically compacted field soils (98. 6 % sand). The ethylene-inhibitor 3,5-diiodo-4-hydroxybenzoic acid (DIHB) (0. 1 µM) was included for each treatment to counteract the negative effects of excess ethylene or compact soils on root elongation. Root elongation was reduced in high ethylene soils by 49 % and high bulk density soils by 44 %. Root ethylene production increased ninefold in roots grown in the high ethylene environment (100 µM), but decreased 80 % in compact soils. The use of DIHB did not alter root length and produced varying results with respect to ethylene production, suggesting an interaction effect involving high amounts of soil ethylene. While ethylene regulates root growth, the physical strength of sandy soils is the major factor limiting root elongation in mechanically impeded soils.